Next generation targeted non-genotoxic conditioning for hematopoietic stem cell and hematopoietic stem cell-based gene therapy - Okalova, Jennifer; Spencer, Trent H.; Chandrakasan, Shanmuganathan (Frontiers in Immunology, 2025)
Hematopoietic stem cell transplant (HSCT) and hematopoietic stem cell (HSC)-based gene therapy, including gene editing approaches, offer a promising strategy for addressing numerous lymphohematopoietic genetic defects. Although significant progress has been made since the first HSCT over 60 years ago, the widespread application of allogeneic HSCT and autologous gene therapy is still hindered by the need for pre-transplant conditioning. The eradication of host HSCs and their progeny is widely thought to be necessary to create “space” in the bone marrow niche and enable long term engraftment of transplanted cells. However, despite decades of research, alkylating agents such as busulfan, melphalan and treosulfan or total body irradiation still remain the backbone of most HSCT condidtioning regimens. These genotoxic conditioning agents are non-targeted and leave patients susceptible to infections, infertility, organ toxicities, and secondary malignancies. As a result, there is an urgent need to develop alternative, non-genotoxic conditioning regimens that can selectively deplete HSCs while sparing cells outside the lymphohematopoietic compartment. A growing body of preclinical and clinical breakthroughs demonstrate the effectiveness of monoclonal antibodies, antibody-drug conjugates, immunotoxins, radioimmunotherapy compounds, and even T cell redirection strategies for achieving targeted HSC elimination. The use of these new agents can transform HSCT, and in this review we aim to highlight the potential and limitations of next-generation, non-genotoxic or minimally toxic conditioning methods. These alternatives to conventional chemoradiation could reduce toxicity and improve the safety of HSC-based gene therapies, ultimately expanding patient access and eligibility for these transformative treatments.